THE MOTHER’S MENSTRUAL CYCLE DIFFERENT BETWEEN MOTHER WHO USE IUD CUT-380A CONTRACEPTION WITH A 3 MOUNTH INJECTABLE CONTRACEPTIVE DEPO VIGESTRON IN MUNJUL VILLAGE PANDEGLANG DISTRIC OF BANTEN 2014. - Mala Kurniati; Deviani Utami (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2014)
Background: One of contraception type is Intra Uterine Device (IUD) wich it one of effective method ofcontraception, used one for long period time. But it has the disadvantage one that the menstrual pattern disturbance. Usinginjectable contraception is also has menstrual pattern disturbance. And the most common side effect of hormonalcontraception are menstrual disorder, nausea may occur at the beginning of use.Objective:To know the difference of menstrual cycle between mother’s who use IUD CuT-380A with a 3 monthinjectable contraceptive Depo Vigestron in Munjul village Pandeglang districk of Banten.Methods:The rearch uses descriptive analitic method with cros sectional approach. Each of population in thisresearchis 34 people for mother who use IUD CuT-380A contraception with a 3 month injectable contraceptive DepoVigestron in Munjul village Pandeglang distric of Banten. The sampling method uses purposive sampling. Data collection bydistributing questioner. Processed by statistic test of independent t test.Result:On the statistical research found p value 0.000 where p value <0.05 wich it means there are significantdifferent between mothers who use IUD CuT-380A contraception with a 3 month injectable contraceptive Depo Vigestron.Conclusions :there is a different between the mother’s menstrual cycle wich uses IUD CuT-380A and a 3 monthinjectable contraceptive Depo Vigestron in Munjul village Pandeglang distric of Banten.